2019
DOI: 10.1038/s41598-019-49902-7
|View full text |Cite
|
Sign up to set email alerts
|

Using wearable devices for assessing the impacts of hair exposome in Brazil

Abstract: Previous studies have shown that physicochemical properties of hair can be impacted by internal and environmental exposures ranging from chemical stressors to weather. Besides the effects on hair, these exposures, termed “exposome”, can act on specific organs including skin, as a synergistic damaging effect of UV exposure and pollution on human surfaces. The combination of several environmental factors such as sun exposure, temperature, relative humidity, air pollution and photo-oxidation caused by ground leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…In [83], the authors reported a research study on multi-stimuli (air temperature and UV) responsive chromism capable of displaying different colours in four different temperature ranges (blue at T < 15 • C, green at 15 • C < T < 33 • C, red at 33 • C < T < 65 • C, and white T > 65 • C) covering a wide range of applications, more than just monitoring environmental conditions. In [84], the authors used different wearables to evaluate the effects of hair exposomes in Brazil. In [85], the authors estimated Heat Exposure of public service workers in Birmingham, Alabama, using thermometers attached to the workers' shoes.…”
Section: Monitoring Of Thermal Ef With Wearablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In [83], the authors reported a research study on multi-stimuli (air temperature and UV) responsive chromism capable of displaying different colours in four different temperature ranges (blue at T < 15 • C, green at 15 • C < T < 33 • C, red at 33 • C < T < 65 • C, and white T > 65 • C) covering a wide range of applications, more than just monitoring environmental conditions. In [84], the authors used different wearables to evaluate the effects of hair exposomes in Brazil. In [85], the authors estimated Heat Exposure of public service workers in Birmingham, Alabama, using thermometers attached to the workers' shoes.…”
Section: Monitoring Of Thermal Ef With Wearablesmentioning
confidence: 99%
“…In [92], the wearable collects ozone concentration data among the other thermal, biometric, and activity data. It is interesting to note the case of study [84] where two wearables, the MyExposome wristband and the 2BTech Personal Ozone Monitor, were used to collect data on environmental aggressors (Polycyclic aromatic hydrocarbons-PAHs, oxygenated PAHs-OPAHs, Polychlorinated biphenyls-PCBs, Pesticides, organophophorous flame retardants-OPFRs, Surface ozone content-SOC) associated with hair damage. In [78], a significant negative correlation was found between the otoacoustic emission levels and the concentration of the styrene urinary metabolites, in workers employed in molding and in artifacts refining.…”
Section: Monitoring Of Air Quality Ef With Wearablesmentioning
confidence: 99%
“…Silicone wristbands appear to be the simplest, least expensive, and easiest to deploy WHD for capturing potential contact and inhalation exposure for a large number of potentially dangerous chemicals, including polyaromatic hydrocarbons (PAHs), polybrominated diphenyl ethers (PBDEs), polychlorinated biphenyls (PCBs), flame retardants, pesticides, pharmaceuticals, personal care products, dioxins, furans, some endocrinedisrupting chemicals, potential carcinogens, and other chemicals (94)(95)(96). Rapid progress also is being made in development of practical WHDs for cholesterol cortisol, glucose, and other parameters (1).…”
Section: Data Collectionmentioning
confidence: 99%
“…The term “structural firefighter” here refers to a firefighter who mainly engaged with building, vehicle, and other urban fires, rather than wildfires. Other personalized passive sampling devices include silicone wristbands ( Anderson et al, 2017 ; Bergmann et al, 2017 ; De Vecchi et al, 2019 ; Dixon et al, 2019 ; Dixon et al, 2018 ; Donald et al, 2016 ; Donald et al, 2019 ; Hammel et al, 2020 ; Hammel et al, 2016 ; Hammel et al, 2018 ; Harley et al, 2019 ; Hendryx et al, 2019 ; Kile et al, 2016 ; Manzano et al, 2019 ; O’Connell et al, 2014a ; Paulik et al, 2018 ; Reddam et al, 2020 ). We previously demonstrated that firefighter PAH exposures differed by fire department call volume, duty shift, and number of fire attacks.…”
Section: Introductionmentioning
confidence: 99%